SPECIES COMPOSITION, STRUCTURE AND QUALITY STATUS OF HEDGES IN BUKOVYNIAN CARPATHIAN REGION OF UKRAINE - Myronchuk, Kateryna; Henyk, Yaroslav; Kurnytska, Marta (My University, 2021)
Object of the study are hedgerows in settlements of Ukrainian Bukovynian Carpathian region (Chernivtsi region of Ukraine). The species and quality composition, spatial, age and ecological structure and ornamental value of hedges. The formation of hedges as an element of landscap-ing the urban ecosystems of the Ukrainian Bukovynian Carpathian region occurred due to the influence of a number of objective (natural and anthropogenic) and subjective factors (traditions, socio-economic conditions and long-term plans for the development of the region, financing of activities for the formation and care of plantings in green spaces). The dendroflora of hedges of urban areas is represented by 32 species of woody plants from 24 genera and 15 families. Carpinus betulus L., Buxus sempervirens L., Cornus alba (L.) Opiz. and Ligustrum vulgare L. are most often used to form hedges. The vast majority of hedges is formed from one species (Chernivtsi – 98.3 %, other towns and villages – 71.1 %), and they are mainly single-row (Chernivtsi – 83.8 %, other towns – 58.2 %, villages – 70.2 %). In the settlements of the region, trimmed hedges predominate (Chernivtsi – 92.1 %, other towns and villages – 75.5 %). Most hedges are mean-height hedges (Chernivtsi – 65.8 %, other towns and villages – 66.9 %). For the formation of a curb hedge, Sріraea media Schmidt., Buxus sempervirens, Ligustrum vulgare are most often used. For first time, comprehensive studies of hedges in the settlements of Chernivtsi region of Ukraine (Bukovynian Carpathian region) were carried out according to their species composition, system, age and environmental structure, height and constitution. The features of functioning in urban ecosystems are established. A comprehensive assessment was made regarding the quality status and ornamental value of hedges in the green zones.
Keywords: dendroflora, decorativeness, functionality of hedges, landscaping, urban.